The Impact of Historical Consciousness and Literacy on Heritage Conservation: A Quantitative Study of High School Students in Ambarawa, Indonesia - Yulianto, Nugroho; Wasino, Wasino; Sutimin, Leo Agung; Susanto, Susanto; Brar, Balraj Singh (History Department, Semarang State University and Historian Society of Indonesia, 2024)
This quantitative study investigated the effect of historical consciousness and literacy on heritage conservation among high school students in Ambarawa, Indonesia. It sought to determine how these educational factors contribute to conservation efforts and their correlation with such activities. The research utilized descriptive statistics, Pearson correlation, and regression analyses to measure historical consciousness and literacy levels and their impact on conservation actions. High levels of historical consciousness and literacy were found among the students, scoring an average of 78 and 82 out of 100, respectively. Notably, a strong positive correlation existed between historical consciousness and conservation actions (0.76) and between historical literacy and conservation efforts (0.69). These elements accounted for 67% of the variance in students’ conservation activities. The findings underscore the significant influence of historical consciousness and literacy on students’ engagement in heritage conservation, highlighting their combined effect in fostering proactive conservation behaviors. The study advocates integrating historical consciousness and literacy into educational programs to enhance youth commitment to heritage conservation. Enhancing these aspects could lead to increased participation in conservation activities, promoting the preservation of heritage sites, and applying historical knowledge in local and global conservation discourses.Studi kuantitatif ini menyelidiki pengaruh kesadaran sejarah dan literasi terhadap konservasi warisan budaya di kalangan siswa sekolah menengah di Ambarawa, Indonesia. Penelitian ini bertujuan untuk mengetahui bagaimana faktor-faktor pendidikan berkontribusi terhadap upaya konservasi dan korelasinya dengan kegiatan-kegiatan tersebut. Penelitian ini menggunakan statistik deskriptif, korelasi Pearson, dan analisis regresi untuk mengukur kesadaran sejarah dan tingkat melek huruf serta dampaknya terhadap tindakan konservasi. Tingkat kesadaran sejarah dan literasi yang tinggi ditemukan di kalangan siswa, dengan skor rata-rata masing-masing 78 dan 82 dari 100. Khususnya, terdapat korelasi positif yang kuat antara kesadaran sejarah dan tindakan konservasi (0,76) dan antara literasi sejarah dan upaya konservasi (0,69). Elemen-elemen ini menyumbang 67% dari keragaman aktivitas konservasi siswa. Temuan ini menggarisbawahi pengaruh signifikan kesadaran sejarah dan literasi terhadap keterlibatan siswa dalam konservasi warisan budaya, dan menyoroti dampak gabungan keduanya dalam mendorong perilaku konservasi proaktif. Studi ini menganjurkan pengintegrasian kesadaran sejarah dan literasi ke dalam program pendidikan untuk meningkatkan komitmen generasi muda terhadap konservasi warisan budaya. Meningkatkan aspek-aspek ini dapat mengarah pada peningkatan partisipasi dalam kegiatan konservasi, mendorong pelestarian situs warisan, dan menerapkan pengetahuan sejarah dalam wacana konservasi lokal dan global.